CO catalytic oxidation on Al-doped graphene-like ZnO monolayer sheets: a first-principles study. Issue 38 (10th September 2015) - Ma, Dongwei; Wang, Qinggao; Li, Tingxian; Tang, Zhenjie; Yang, Gui; He, Chaozheng; Lu, Zhansheng
Abstract : Three mechanisms for CO catalytic oxidation on Al-doped g-ZnO monolayer sheets were comparably studied, among which the Eley–Rideal mechanism is both energetically and dynamically more favorable. Abstract : The graphene-like ZnO (g-ZnO) monolayer sheet is a new class of two-dimensional materials with unique properties, which are still largely unexplored. This work studied the modulation of electronic structures and chemical activities of the g-ZnO monolayer sheet by substituting Al for host Zn atoms. It is found that replacing Zn with Al atoms is both energetically and dynamically highly favorable. Al doping introduces electrons into the conduction band of the g-ZnO monolayer sheet, which should significantly enhance the conductance and the chemical activity of the sheet. The CO oxidation by the lattice O atoms via the Mars–van Krevelen mechanism, and by the adsorbed O2 via the Langmuir–Hinshelwood and Eley–Rideal mechanisms were comparably studied. The Al-doped g-ZnO monolayer sheet shows good catalytic activity for the CO oxidation via the more favorable Eley–Rideal mechanism with a two-step route. The study presents an effective strategy to tune the electronic structure and the chemical activity of the g-ZnO nanosheets, and gives us an insight into the mechanism of Al-doped ZnO nanostructures sensing reducing gases.